The clinical relevance of ferritin concentration in the cerebrospinal fluid. - Sindic, C J (1981)
By means of a new technique (Particle Counting Immunoassay), we have determined the level of ferritin in 470 samples of cerebrospinal fluid of patients with various neurological disorders. The median value obtained in a control group was 2.3 ng/ml with an upper limit at 5.5 ng/ml. the concentrations in the serum and cerebrospinal fluid were independent, but that in cerebrospinal fluid correlated with its total protein content. High values of ferritin were found in infectious meningo-encephalitis, in vascular diseases of the central nervous system, and, unexpectedly, in several cases of dementia without obvious vascular pathology.